PROFITABILITY DISCLOSURE AS MEDIATOR BETWEEN FINANCIAL FACTORS AND TAX AVOIDANCE PRACTICES - Dewi, Sari; Sudirman; Karjantoro, Handoko (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2025)
Purpose - The study examines tax avoidance practices among companies listed on the Indonesia Stock Exchange (2019–2023), focusing on leverage, company size, and sales growth, with profitability as a mediating factor. Tax avoidance, though legal, exploits gaps in regulations, affecting governance and revenue. The research aims to understand these relationships and provide insights for policymakers and stakeholders in improving tax compliance. The purpose of this research is to analyse the role of leverage, company size, and sales growth on tax avoidance, with profitability as a mediator. Research Method - This research uses secondary data from companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2023. The analysis method is multiple linear regression using Eviews. Findings - Leverage has a significant effect on tax avoidance, while company size and sales growth have no significant effect on tax avoidance. Profitability can mediate tax avoidance, with mediation variable leverage having a significant effect on tax avoidance, but profitability cannot mediate between company size and sales growth. Implication - This research fills a gap in the literature by highlighting the importance of transparency in profitability and how it mediates the influence of financial factors on tax avoidance. This study has the potential to pave the way for further research on transparency and financial information disclosure in reducing tax avoidance practices.